Bilateral adrenal haemorrhage after a high energetic trauma: a case report and review of current literature. Issue 2 (3rd March 2020) - Jimidar, N.; Ysebaert, D.; Twickler, M.; Spinhoven, M.; Dams, K.; Jorens, P. G.
Abstract: Most adrenal injuries are asymptomatic. In traumatic events, adrenal haemorrhage is very likely to be accompanied by injuries to other organs. Isolated adrenal injury after trauma is very rare and mostly unilateral. We report a case of a 44-year-old male who suffered a major traffic accident with multiple trauma, including a bilateral adrenal haemorrhage. This caused a primary adrenal insufficiency, as proven with a cortisol stimulation test with synthetic corticotrophin. Bilateral adrenal haemorrhage is a very rare but potentially fatal disorder and should not be missed. This case illustrates that early diagnosis and prompt treatment with hydrocortisone may contribute to a beneficial outcome.